Kansas Land Prices and Cash Rental Rates - Dhuyvetter, Kevin C.; Kastens, Terry L. (My University, 1999)
This farm management guide reports Kansas land prices from 1980-1999 and cash rental rates for 1980-1998. The data is meant to be useful to farm managers.
MF1100_1999_10
Keywords: MF1100; Economics; MF